Analysis of interleukin 7 and platelet-derived growth factor-BB mRNA expression as potential markers in erythema nodosum leprosum (Dermatology Reports, 2023)
Erythema nodosum leprosum (ENL) is an immunological complication of leprosy characterized by acute inflammation of the skin, nerves, and other organs. Identifying laboratory parameters is important for early diagnosis of leprosy reactions. Various cytokine biomarkers have been examined and only a few studies have reported on angiogenesis in leprosy. This study aims to understand the pathomechanism of ENL by examining IL-7 and plateletderived growth factor (PDGF)-BB mRNA expression that can be the development and consideration of new effective therapies to prevent reactions, recurrences, and defects in leprosy. The study used a cross-sectional analytic design. Sampling was done by peripheral blood from the patient and measuring mRNA expression with specific primers RT-PCR. The expression of mRNA IL-7 and PDGF-BB was significantly different between multibasilar patients without reaction and with ENL reaction, where there was an increased expression in ENL patients. This could be used as the development of potential biomarkers in ENL and development of new therapeutic intervention pathways in ENL.